"De gustibus errari (pot)est": utility misprediction, preferences for well-being and life satisfaction - Bechetti, Leonardo; Conzo, Pierluigi (Rome, 2014)
"The life satisfaction literature generally focuses on how life events affect subjective well-being. Through a contingent valuation survey we test whether well-being preferences have significant impact on life satisfaction. A sample of respondents is asked to simulate a policymaker decision consisting in allocating scarce financial resources among 11 well-being domains. Consistently with the utility misprediction hypothesis, we find that the willingness to invest more in the economic well-being domain is negatively correlated with life satisfaction. Our findings are shown to be robust when we account for unobservables related to economic fragility and non-random sample selection. Revers e causality and omitted variable bias are controlled for with instrumental variables and a sensitivity analysis on departures from exogeneity assumptions. Subsample estimates document that the less educated are more affected by the problem."